Pemanfaatan Aplikasi Kahoot Sebagai Media Pembelajaran Pada Mata Pelajaran Informatika Siswa Kelas X Di SMA Kristen 1 Salatiga - Desi Desi; Rissal Efendi (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research analyzes the utilization of the Kahoot application as a learning media for Informatics in 10th-grade students at SMA Kristen 1 Salatiga. The research method employed is a quantitative approach with a single experimental group as respondents, involving 60 students. In the implementation of the Kahoot application in the learning process, Kahoot is integrated into the Informatics curriculum as an additional learning media. The results of the research indicate a significant improvement in learning achievement after using Kahoot. The students also responded positively to the utilization of Kahoot as a learning media. They perceived Kahoot as a fun and effective method to enhance learning motivation and active engagement in the Informatics learning process. This research also demonstrates that Kahoot can be an effective tool to improve student learning achievement and engagement in Informatics, as evidenced by the analysis using SPSS. In the context of SMA Kristen 1 Salatiga, Kahoot provides positive benefits for the learning process and serves as a valuable resource for both teachers and students. Keywords: Kahoot application, learning media, Informatics, 10th-grade students, SMA Kristen 1 Salatiga.